Development of Cystoisospora felis in Cell Culture and in vitro Formation of Monozoic Tissue Cysts - Ferreira, Rachel; Borges-Silva, Waléria; de Jesus, Rogério F.; Gondim, Luís F. P. (Frontiers in Veterinary Science, 2019)
Cystoisospora felis is a coccidian parasite commonly found in feces of domestic cats. Infection in cats occurs by ingestion of sporulated oocysts or consumption of rodents infected by the parasite. Scarce information is available about extraintestinal stages of C. felis in naturally infected intermediate hosts, as well as in cell culture. The aim of the current work was to investigate the development of C. felis in Vero cells (African green monkey kidney) and MDCK cells (Madin-Darby canine kidney). Cell monolayers were inoculated with mechanically released sporozoites of C. felis, and parasite growth was daily examined using light microscopy. After cell invasion, only parasitophorous vacuoles containing a single zoite were observed. Five days post-inoculation with sporozoites, unstained cell monolayers were evaluated by differential interference contrast (DIC), and also by Romanovsky stain using conventional light microscopy. Single zoites, each surrounded by a cyst wall, were observed by both methods. Multiplication by endodyogeny did not occur in any cell monolayer. Treatment of encysted parasites with HCl-pepsin for 15 min led to dissolution of the cyst wall and release of intact and motile zoites. To our knowledge, this is the first demonstration of in vitro production of monozoic tissue cysts of C. felis. As kittens commonly shed C. felis in their feces, oocysts are easily available for in vitro production of monozoic tissue cysts of the parasite. Development of C. felis in cell culture may be employed as a model on tissue cyst formation of Cystoisospora spp. and closely related coccidia.